The intracellular detection of MIP-1beta enhances the capacity to detect IFN-gamma mediated HIV-1-specific CD8 T-cell responses in a flow cytometric setting providing a sensitive alternative to the ELISPOT - Kutscher, Sarah (BioMed Central, 2008)
BACKGROUND: T-cell mediated immunity likely plays an important role in controlling HIV-1 infection and progression to AIDS. Several candidate vaccines against HIV-1 aim at stimulating cellular immune responses, either alone or together with the induction of neutralizing antibodies, and assays able to measure CD8 and CD4 T-cell responses need to be implemented. At present, the IFN-γ-based ELISPOT assay is considered the gold standard and it is broadly preferred as primary assay for detection of antigen-specific T-cell responses in vaccine trials. However, in spite of its high sensitivity, the measurement of the sole IFN-γ production provides limited information on the quality of the immune response. On the other hand, the introduction of polychromatic flow-cytometry-based assays such as the intracellular cytokine staining (ICS) strongly improved the capacity to detect several markers on a single cell level. RESULTS: The cumulative analysis of 275 samples from 31 different HIV-1 infected individuals using an ICS staining procedure optimized by our laboratories revealed that, following antigenic stimulation, IFN-γ producing T-cells were also producing MIP-1β whereas T-cells characterized by the sole production of IFN-γ were rare. Since the analysis of the combination of two functions decreases the background and the measurement of the IFN-γ+ MIP-1β+ T-cells was equivalent to the measurement of the total IFN-γ+ T-cells, we adopted the IFN-γ+ MIP-1β+ data analysis system to evaluate IFN-γ-based, antigen-specific T-cell responses. Comparison of our ICS assay with ELISPOT assays performed in two different experienced laboratories demonstrated that the IFN-γ+ MIP-1β+ data analysis system increased the sensitivity of the ICS up to levels comparable to the sensitivity of the ELISPOT assay. CONCLUSION: The IFN-γ+ MIP-1β+ data evaluation system provides a clear advantage for the detection of low magnitude HIV-1-specific responses. These results are important to guide the choice for suitable highly sensitive immune assays and to build reagent panels able to accurately characterize the phenotype and function of responding T-cells. More importantly, the ICS assay can be used as primary assay to evaluate HIV-1-specific responses without losing sensitivity in comparison to the ELISPOT assay.